Direct in vivo reprogramming to relieve tissue ischemia via induced vasculogenesis - Yoder, Mervin C; Sen, Chandan K (Molecular therapy, 2025)
There is an ongoing need for innovative cell and regenerative medicine therapies to promote vascular repair and regeneration to meet the growing global health concern of ischemic cardiovascular diseases. Direct reprogramming of somatic cells into an induced pluripotent state caused scientists to reconsider prior theories of cell differentiation and develop approaches to directly reprogram cells in vivo into other states or fates to adaptively replace cells lost to aging or disease. While direct in vivo reprogramming of fibroblast to cardiomyocytes, neurons, or pancreatic beta islet cell states has been studied since 2008, direct in vivo reprogramming of fibroblasts into induced vasculogenic cells was not reported until 2017. This review provides a brief overview of the field of in vitro direct reprogramming of fibroblasts into induced endothelial cells over the past decade and identifies key similarities and differences in approaches. The primary focus of this review is to discuss in detail 4 published reports of direct in vivo reprogramming of fibroblasts into vasculogenic cell states and identify a series of questions for future studies that will clarify the reprogrammed cells and potential for using these approaches for translation into larger preclinical models or human subjects.